SAT0392 ICG-enhanced fluorescence optical imaging in clinical remission: Longitudinal data in RA and PSA patients with pre/post comparisons. (23rd January 2014) - Werner, S.G.; Spiecker, F.; Hermsen, C.; Bahner, M.; Backhaus, M.; Langer, H.-E.
Abstract : Background: ICG (Indocyanine-Green) fluorescence optical imaging (FOI) is a novel imaging technology in rheumatology (1) and may be a suitable tool for monitoring of disease activity and treatment response (2). Objectives: This is the first study with longitudinal data of FOI in RA and PsA patients in clinical remission. The objective was to compare clinical activity and FOI findings before, at and after achievement of clinical remission. Methods: A total of 113 subjects were included in a prospective study of FOI in RA and PsA patients with low disease activity (inception cohort: disease activity ≤1 at global assessment by patient or physician, NRS 0-10). All patients received a clinical examination by an independent investigator, and blood samples were taken for measurement of systemic inflammation (ESR, CRP). Inflammatory activity in FOI was assessed by an experienced reader using the semiquantitative fluorescence optical imaging activity score (FOIAS) (1), which comprises of the measurement of joint-related fluorescence signals in an automatically generated composite image (Prima Vista Mode, PVM) and in three predefined phases of FOI (P1, P2, P3).In 38 subjects with DAS28 remission (DAS28 <2, 6) at least one FOI study had been performed either prior to remission (≥3 months, n=34) or at follow-up (≥3 months, n=31). 11 subjects had sequential FOI examinations prior to and after remission. The sample with a total of 103 FOI studies was selected for further analysis. Results: In most patients clinical and FOI activity were following a uniform trend (table). Cross-sectional analysis revealed a moderate correlation of (r=0.4) of DAS28 and FOIAS. FOI evidence of subclinical disease activity was more pronounced in the various phases of a FOI sequence than in PVM. 11 subjects had treatment changes (reduction of DMARDs, tapering of steroid dose) due to clinical remission. In individual patients FOIAS increased with ongoing clinical remission. In joint-to-joint comparisons, those patients showed at first decreasing FOI activity in originally symptomatic joints with the achievement of remission. When treatment was reduced at this stage, then even clinically still asymptomatic patients demonstrated an increase in FOI activity in those same joints. Conclusions: FOI is a useful tool for monitoring disease activity and treatment response in RA and PsA patients. Most subjects with clinical remission showed residual activity in FOI. Pre/post-comparisons in individual patients suggest that subclinical disease activity in FOI may announce an initiating relapse in patients with premature withdrawal of treatment. References: Werner SG, Langer HE, Ohrndorf et al. Inflammation assessment in patients with arthritis using novel in vivo fluorescence optical imaging technology. Ann Rheum Dis Oct 2011, Epub ahead of print. Werner S et al. 2011 ACR/ARHP Annual Scientific Meeting, Chicago, IL, Nov. 4 -9, 2011, Poster 199 Disclosure of Interest: S. Werner Grant/Research support from: Pfizer, F. Spiecker: None Declared, C. Hermsen: None Declared, M. Bahner Shareholder of: mivenion GmbH, M. Backhaus Grant/Research support from: Pfizer, H.-E. Langer Grant/Research support from: Pfizer